(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study was administered to compare the effectiveness of yogic awareness between the urban and rural male populations of the Meerut district. Sample men from rural and urban areas were randomly selected for the response, where371 men responded due to the various limitations of the study.A self-made questionnaire on the Effectiveness of Yogic awareness on Overall Health and well-being was prepared and administered in rural and urban areas of Meerut. Welch's t-test was applied to analyze the data and the results indicate that there is a significant between the means of male andf emale.Hence null hypothesis was rejected and the alternative hypothesis was accepted. Conclusion: There is a difference between the awarenessimpact of yoga on the overall health and wellness of males and females during the COVID-19pandemic.